A Grid–QoS Decision Support System using Service Level Agreements - Bandini, Matheus; Mury, Antonio Roberto; Schulze, Bruno; Salles, Ronaldo (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2009: Anais do XXXVI Seminário Integrado de Software e Hardware, 2009)
The availability of better services and products has become a challenge in all segments, from economics to high technology. This paper proposes an approach to Quality of Service for Grid Computing that involves the analysis of the grid resources and the categorization of types of services into Service Level Agreements (SLAs). This work focuses on the definition of grid indicators to create a Decision Support System that helps to identify the Quality of Service offered by the resources available in the grid, as well as the improvement needed for these services. The system also includes benefits for grid users, such as the quality of the information provided about the grid resources, which allows users to manage and use the available resources in an easy way, improving the system’s QoS from the user’s point of view.